Protective effect of n-acetyl-L-cysteine and rosuvastatin against oxidative stress in fibroblasts from asymptomatic patients with X-ALD: a preliminary study - Marchetti, Desiree; Ribas, Graziela S; Donida, Bruna; Brito, Verônica; Moura, Dinara J; Coelho, Daniella M; Machado, Andryele Z; Kessler, Rejane G; Coitinho, Adriana S; Vargasa, Carmen R (Clinical and Biomedical Research, 2021)
Introduction: Several studies in the literature have evaluated the role of oxidative stress and adjuvant therapies for X-linked adrenoleukodystrophy (X-ALD). Here, we investigated whether n-acetyl-L-cysteine (NAC) and rosuvastatin (RSV) could influence the generation of reactive species, redox status and nitrative stress in fibroblasts from asymptomatic patients with X-ALD. Methods: Skin biopsy samples were cultured and treated for 2 hours (37 °C) with NAC and RSV. Results: X-ALD fibroblasts generated high levels of reactive oxygen species. These levels were significantly lower in fibroblasts treated with NAC and RSV relative to untreated samples. The X-ALD fibroblasts from asymptomatic patients also had higher catalase activity, and only NAC was able to increase enzyme activity in the samples. Conclusion: Our results indicated that NAC and RSV were able to improve oxidative stress parameters in fibroblasts from asymptomatic patients with X-ALD, showing that adjuvant antioxidant therapy may be a promising treatment strategy for asymptomatic patients with this disease.